PI4‐kinase and PfCDPK7 signaling regulate phospholipid biosynthesis in Plasmodium falciparum. (6th December 2021) - Maurya, Ranjana; Tripathi, Anuj; Kumar, Manish; Antil, Neelam; Yamaryo‐Botté, Yoshiki; Kumar, Praveen; Bansal, Priyanka; Doerig, Christian; Botté, Cyrille Y; Prasad, T S Keshava; Sharma, Pushkar
Abstract: PfCDPK7 is an atypical member of the calcium‐dependent protein kinase (CDPK) family and is crucial for the development of Plasmodium falciparum . However, the mechanisms whereby PfCDPK7 regulates parasite development remain unknown. Here, we perform quantitative phosphoproteomics and phospholipid analysis and find that PfCDPK7 promotes phosphatidylcholine (PC) synthesis by regulating two key enzymes involved in PC synthesis, phosphoethanolamine‐N‐methyltransferase (PMT) and ethanolamine kinase (EK). In the absence of PfCDPK7, both enzymes are hypophosphorylated and PMT is degraded. We further find that PfCDPK7 interacts with 4'‐phosphorylated phosphoinositides (PIPs) generated by PI4‐kinase. Inhibition of PI4K activity disrupts the vesicular localization PfCDPK7. P. falciparum PI4‐kinase, PfPI4K is a prominent drug target and one of its inhibitors, MMV39048, has reached Phase I clinical trials. Using this inhibitor, we demonstrate that PfPI4K controls phospholipid biosynthesis and may act in part by regulating PfCDPK7 localization and activity. These studies not only unravel a signaling pathway involving PfPI4K/4'‐PIPs and PfCDPK7 but also provide novel insights into the mechanism of action of a promising series of candidate anti‐malarial drugs. Synopsis: PfPI4K and PfCDPK7 regulate the development of the malaria parasite Plasmodium falciparum by promoting phospholipid biosynthesis. PI4‐Kinase regulates the localization and activity of protein kinase PfCDPK7 via 4'‐PIPs. PfCDPK7 promotes phosphatidylcholine (PC) synthesis by targeting key enzymes involved in the synthesis of this phospholipid. PI4‐K promotes PL biosynthesis in P. falciparum and its regulation of PfCDPK7 activity contributes to this process. Abstract : PfPI4K and PfCDPK7 regulate the development of the malaria parasite Plasmodium falciparum by promoting phospholipid biosynthesis.